Local and generalized height-diameter equations for Pinus patula Schl. et Cham. in Veracruz, Mexico - Hernandez Ramos, Jonathan; Avilés-Castillo, Alejandro; García-Magaña, J. Jesús; Hernández-Ramos, Adrián; García-Cuevas, Xavier; Flores-López, Celestino (Ecosistemas y Recursos Agropecuarios, 2020)
In forest management, reliable and accurate estimation of tree height is essential. Therefore, the objective was to adjust local and generalized equations of total height-normal diameter for Pinus patula Schl. et Cham. in the ejido Monte Grande, municipality of Ixhuacán de los Reyes, Veracruz, Mexico. With information of 1 825 pairs of full height-normal diameter data from 150 sampling sites with a dimension of 500 m2 from the forest inventory, nine local-type and three generalized height-normal diameter equations were adjusted. The selection of the best equation was made by verifying the highest adjusted coefficient of determination, the lowest root of the mean square of the error and the significance of the parameters, in addition to verifying compliance with the normality, homoscedasticity and self-regression assumptions. correlation. The local equations explain 62.2% of the sample variability, while the generalized equations describe 74.3% by adding the variables of average site height, where there is no violation of the regression assumptions. The average bias per estimate is 0.046 and 0.285 m for local and generalized expression, respectively. The graphic analysis of the estimates in all cases showed adequate trends to the variability of the sample, therefore, they can be used reliably to accurately predict the height as a function of the normal diameter in P. patula stands, either in forest inventories or volume estimation in forest management programs